2013
DOI: 10.1002/jmri.24300
|View full text |Cite
|
Sign up to set email alerts
|

High resolution diffusion tensor imaging of human nerves in forearm

Abstract: Purpose To implement high resolution diffusion tensor imaging (DTI) for visualization and quantification of peripheral nerves in human forearm. Materials and Methods This HIPAA-compliant study was approved by our Institutional Review Board and written informed consent was obtained from all the study participants. Images were acquired with T1-and T2-weighted turbo spin echo with/without fat saturation, short tau inversion recovery (STIR). In addition, high spatial resolution (1.0 × 1.0 × 3.0 mm3) DTI sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 26 publications
3
55
0
Order By: Relevance
“…Overall, this study's findings support the hypothesis that combining the two denoising techniques effectively improves SNR and nerve conspicuity, overcoming challenges in accurately determining measures of nerve integrity from quantitative dMRI within a clinically feasible scan time. Importantly, the results support previous findings that SNR affects derived FA values and may at least partially explain previously reported variability in FA of nerves in healthy controls . Combining PCA and genSD denoising methods resulted in FA values similar to the benchmark (ie, "average" dataset), thereby improving the diagnostic accuracy of dMRI of peripheral nerves within the extremities.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, this study's findings support the hypothesis that combining the two denoising techniques effectively improves SNR and nerve conspicuity, overcoming challenges in accurately determining measures of nerve integrity from quantitative dMRI within a clinically feasible scan time. Importantly, the results support previous findings that SNR affects derived FA values and may at least partially explain previously reported variability in FA of nerves in healthy controls . Combining PCA and genSD denoising methods resulted in FA values similar to the benchmark (ie, "average" dataset), thereby improving the diagnostic accuracy of dMRI of peripheral nerves within the extremities.…”
Section: Discussionsupporting
confidence: 86%
“…Establishing normative DTI values is crucial to increase the confidence of detecting pathology, particularly in milder forms of peripheral neuropathy that may only result in small changes in DTI parameters. Multiple studies, however, have demonstrated a wide range in DTI values of upper extremity peripheral nerves in healthy cohorts . There is significant variation in trends of DTI metrics, with most studies showing a decrease in FA and increase in ADC in the median nerve when moving from proximal to distal in the forearm, an increase in FA with no difference in ADC, and a decrease in ADC with no change in FA in normal volunteers.…”
Section: Peripheral Nerve Dti Applicationsmentioning
confidence: 99%
“…Ultimately, more studies are needed to confirm a trend. Moreover, there are inter‐nerve DTI differences between the ulnar, median, and radial nerves . Some of this variability may be explained by insufficient spatial resolution and SNR.…”
Section: Peripheral Nerve Dti Applicationsmentioning
confidence: 99%
“…This method is useful to provide anatomical data and to detect pathologies such as tumors that affect the continuity of nerves 18, 19. More recently, diffusion tensor imaging of peripheral nerves has been introduced as a tool to quantify nerve damage and regeneration 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%